The Influence of Position of Durian in Determination of Ripeness of Durian Non-Destrucyively by Ultrasonic Wave - Bambang Haryanto; I Wayan Budiastra; Amoranto Trisnobudi (Jurnal Keteknikan Pertanian, 2000)
The study was conducted to assess the influence of durian 's position toward transmission properties of ultrasonic wave for determination of the fruit ripeness using non-destructiive technique. Three ripe and unripe durian were used to assess transmittance wave that was passed the durian. The measurement was conducted at 3 peak and valley positions and it was repeated 20 times. The result showed that position durian 's inJluenccad thetransmissions of ultrasonic wave. Mo mzJ a (attenuation) values can be used as indicator for durian ripeness. Ripe durian tends to have highera value than unripe durian.